Metastatic Renal Cell Carcinoma of the Nasal Septum: A Case Report - Mustafa Aslıer; Mustafa Cenk Ecevit (Turkish Archives of Otorhinolaryngology, 2018)

(untitled)
Metastatic lesions of the nasal cavity and paranasal sinuses are rare tumors. Carcinomas originating from intrapelvic organs play an important role in the differential diagnosis of these masses because of their paradoxic spread to the head and neck region. In this study we report a case with metastatic renal cell carcinoma of the caudal nasal septum.